El legado de las Siete Leyes: una reevaluación de las aportaciones del constitucionalismo centralista a la historia constitucional mexicana - Andrews, Catherine (El Colegio de México, A.C., 2019)
The objective of this article is to analyze the primary characteristics of the constitution of the Seven Laws (1836) and evaluate its impact on later Mexican constitutionalism. The historiographical consensus is that the Seven Laws constituted the first constitutional text written by the conservative faction and, therefore, that this constitution did not have an impact on the development of the liberal project that resulted in the Constitution of 1857. The research presented herein shows that this assessment is false and that the constitutional ideas of the Seven Laws influenced both the Organic Bases and both liberal and later conservative constitutionalism.